Pemberdayaan Santripreneur melalui Produksi “D’box Crispy“ di Pondok Pesantren Sunan Drajat Lamongan - Abdul Mun'im; Abdullah As’ad; Lutfi Husain Mabruri; Misbahul Mun’im Fattah; Muh Mu’amar Al Khotimi (KERIS : Journal of Community Engagement, 2021)
Santripreneurs are very important in Islamic boarding schools and at Pondok Pesantren Sunan Drajat is a boarding school located in the village of Banjarwati, Paciran sub-district which is in a large complex and is currently introducing students to the business sector. The Sunan Drajat Islamic Boarding School will later become an example for other pesantren, especially those in Lamongan and East Java in an effort to improve the quality of students who have an entrepreneurial spirit. The obstacle faced is the lack of students who have an entrepreneurial spirit. So the solution that can be given is to hold Santripreneur Empowerment through the Production of "D'BOX CRISPY" with the students of the Sunan Drajat Islamic Boarding School. The purpose of this program is to empower the students of the Sunan Drajat Islamic Boarding School in instilling the entrepreneurial spirit in the program. Then the method used is to make banana chips which are developed into banana chips and later learn to introduce or promote the products they made earlier. Other than that, the result of this program is that the Sunan Drajat Islamic Boarding School can improve students who have an entrepreneurial spirit and maintain and even develop them Santripreneur sangatlah penting dalam Pondok Pesantren dan di Pondok Pesantren Sunan Drajat adalah pondok pesantren yang terletak di desa banjarwati kecamatan paciran yang mana berada di kompleks yang luas dan baru baru ini sedang mengenalkan santri dalam bidang bisnis . Pondok Pesantren Sunan Drajat nantinya akan menjadi contoh untuk pesantren lain khususnya yang ada di lamongan dan jawa timur dalam upaya peningkatan kualitas santri yang berjiwa interpreneur. Adapun kendala yang dihadapi adalah kurangnya santri yang mempunyai jiwa interpreneur. Sehingga solusi yang dapat di berikan adalah dengan mengadakan Pemberdayaan Santripreneur Melalui Produksi “D’BOX CRISPY” dengan bersama santri Pondok Pesantren Sunan Drajat. Tujuan dari program ini adalah untuk memberdayakan santri Pondok Pesantren Sunan Drajat dalam menanamkan jiwa jiwa interpreneur dalam progrm tersebut. Kemudian metode yang digunakan adalah dengan melakukan pembuatan pelapah pisang yang di kembangkan menjadi kripik pelapah pisang dan nantinya juga belajar memperkenalkan atau mempromosikan produk yang dibuatnya tadi. Lain daripada itu hasil dari program ini adalah Pondok Pesantren Sunan Drajat dapat meningkatkan santri santri yang berjiwa interpreneur.